RIWAYAT PEMERIKSAAN KEHAMILAN DAN PEMBERIAN ASI EKSKLUSIF - Aswita Amir; Siti Nur Rochimiwati; Manjilala Manjilala; Musdalifah Muharrikah (Media Gizi Pangan, 2017)
Background : Antenatal care is important to do the mother during pregnancy to detect high risk. Exclusive breastfeeding educational purposes, namely in order to have sufficient knowledge of the mother after giving birth to exclusive breastfeeding to their children.Objectives  : The purpose of this study to describe antenatal care and exclusive breastfeeding in infants aged 6-12 months in the Village Mangga Tiga Paccerakkang Biringkanaya District of Makassar.Methode    : This type of research is observational research with descriptive, the sample in this research that mothers of children aged 6-12 months in l Bougenvil 2 and Bougenvil 30 Housing Mangga Tiga Village Paccerakkang Biringkanaya Makassar City Subdistrict 30 people with method purposive sampling. antenatal care and exclusive breastfeeding was obtained by interview using a questionnaire.Result     : Processing antenatal care and exclusive breastfeeding is processed with a view of respondents and data analysis using SPSS then presented through tables and narrative.The results showed that as many as 66.7% of prenatal care, exclusive breastfeeding education as much as 100%, exclusive breastfeeding as much as 30% and as much as 70% exclusive breastfeeding.Keywords: Antenatal Care, Breastfeeding Exclusive, Education